Civil Society and Human Rights as Part of the Neoliberal Narrative: An Export to the Russian Federation1 - Seixas, Eunice Castro (Academic Quarter | Akademisk kvarter, 2011)
In Civil Society and Human Rights as Part of the Neoliberal Narrative: An Export to the Russian Federation by Eunice Castro Seixas we find a quite different global narrative. Its starting point is that civil society and human rights are global narratives, presumed universal narratives that are exported to the South and more recently to Eastern European borders, as part of the "global governance" ideology. Seixas suggests that human rights and civil society liberal narrative are being transformed and re-appropriated in today's Russian society, by the State, the Church and civil society organizations. Although there is not a full refusal of these liberal concepts by Russian human rights organizations, neither is there a clear alternative discourse.